Gender Equality in the Foreign Language Textbooks of Indonesian Junior High Schools - Ambo Dalle; Baso Jabu; Siti Suwadah Rimang (Universitas Negeri Makassar, 2023)
The objectives of this research were (1) to find out the gender representation of men and women in the English curriculum documents; and (2) to find out the distribution of men and women in the foreign curriculum documents. The sample consisted of three most common books used in junior high schools representing grade VII, VIII and IX. The data on gender equality were analyzed through content analysis approach. The results of the research showed that: (1) the lexical representation of men compared to women in the textbook were higher than women lexical related issues; (2) the distributions of men were also much wider compared to the distribution of women. The word ‘he’ is used much more frequently that the used of word ‘she’ in different context of reading, writing, listening and speaking